Simple and efficient approach to 1,3-aminoalcohols: application to the synthesis of (+)-negamycin - Naidu, S. Vasudeva; Kumar, Pradeep (Tetrahedron Letter, 2007)
A short and practical enantioselective synthesis of (+)-negamycin has been achieved in high enantio- and diastereomeric excess using an iterative Jacobsen's hydrolytic kinetic resolution as the key step. (C) 2007 Elsevier Ltd. All rights reserved.